Korelasi Antara Locus of Control Internal dengan Perilaku Prososial pada Relawan MRI Surabaya (SUKMA : Jurnal Penelitian Psikologi, 2020)
The high incidence of covid 19 and the scarcity of masks and handsanitizers overwhelmed medical personnel. Where the number of medical calm and the number of covid patients 19 is not balanced. So that there is a need for volunteers to assist in handling covid 19. Where the form of activities carried out by volunteers is included in prosocial behavior. Prosocial behavior by the community has increased. This can be seen from the high level of community participation in volunteering and the number of donations for handling Covid 19, which is increasing every day. This study aims to determine the relationship between internal locus of control with prosocial behavior in volunteers. The method in this study is a quantitative method using 101 MRI volunteers handling covid 19 subjects taken using simple random sampling technique. Data analysis using the Spearmans Brown test with the help of SPSS. The results showed a significant positive relationship between internal locus of control with prosocial behavior with a correlation coefficient of 0.476 and a significance of 0.000. So it can be concluded that the existence of internal locus of control in volunteers can improve prosocial behavior.Keywords : internal locus of control., prosocial behavior